Factors Influencing Farmers' Decision to Enter Forward Contracts: A case study in the Vanni Region of Northern Sri Lanka - Umashankar, K.; Arunkumar, P. (Sri Lanka Agricultural Economics Association, 2013)
It is inferred from experience that when the returns from the effort applied in producing food is not sufficient to lift the farmer above want, the motivation in farming collapses and the cultivator looks to other sources for survival. Hence it is quite important to have an organized marketing practice to concentrate on sustainable increased income. Beyond all the criticism of the contract farming practice, with certainty it is providing an opportunity in bringing the far away international markets within the reach of the peasants which will in turn fetch a steady and enhanced income for their livelihood. This research attempted to identify the factors influencing farmers' selection to enter into forward contra ing agreements. Mullaithivu District in the Northern Province of Sri Lanka was selected as the study area. Farmers in this region have been rendered destitute by the war and tidal wave disasters and are desperately struggling to lift themselves by their boot strings. It is notable that Hayleys PLC offered a contract opportunity to each and every vegetable farmer in the locality to cultivate gherkins. The opportunity was seized by a few although many didn't take up. Data from 174 farmers selected randomly were collected using a structured questionnaire. Data were analyzed using a logistic regression model. Marginal effects rather than deliberating on the logit parameters were used in interpretation. The results revealed that a 1% increase in the household size, years of experience in farming, distance to market, and credit availability are factors which positively affect the entry into contract farming by 4.1%, 1.5%, 6.25% and 23.3% respectively at the 10% significant level. Conversely a 1% increase in the Age, years of education of the farmer and opportunities for off-farm income all affect negatively entry into contract farming by 1.68%, 4.59% and 1.01% at the significant level of 5%, 1% and 5% respectively. Selection of full time farmers with large household sizes from rural areas where market access is poor and grant them credit facility would encourage greater number of farmers to enter into contract farming.
Keywords: Off-farm income; Production credit; Gherkins; Binary logistic regression; Marginal effects